2022
DOI: 10.21037/tlcr-22-54
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases, patterns of intracranial progression, and the clinical value of upfront cranial radiotherapy in patients with metastatic non-small cell lung cancer treated with PD-1/PD-L1 inhibitors

Abstract: Background: Despite the emergence of programmed death 1/programmed death-ligand 1 (PD-1/PD-L1) inhibitors in the treatment of non-small cell lung cancer (NSCLC) patients with brain metastases (BMs), knowledge gaps remain regarding the impact and timing of cranial radiotherapy for patients receiving anti-PD-1/PD-L1 therapy.Methods: Data were collected from 461 consecutive patients who received anti-PD-1/PD-L1 therapy for metastatic NSCLC at three institutions between June 2017 and September 2020. Intracranial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…After excluding 139 studies because the article type was not suitable for inclusion (including 13 case studies, 4 meta-analyses, 13 single-arm studies, 17 studies on other tumor types, 22 conference papers with abstracts only, 12 phase I studies, 15 ongoing studies, 42 reviews, and 1 comment), 3 RCTs and 12 NRCTs remained. A total of 15 clinical studies were reported in 16 publications ( Figure 1 ) ( Kataoka et al, 2017 ; Shaverdian et al, 2017 ; Tamiya et al, 2017 ; Fiorica et al, 2018 ; Theelen et al, 2019 ; Welsh et al, 2020 ; Hosokawa et al, 2021 ; Metro et al, 2021 ; Samuel et al, 2021 ; Sheng et al, 2021 ; Theelen et al, 2021 ; Öjlert Å et al, 2021 ; Guo et al, 2022 ; Qiang et al, 2022 ; Schoenfeld et al, 2022 ; Wang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…After excluding 139 studies because the article type was not suitable for inclusion (including 13 case studies, 4 meta-analyses, 13 single-arm studies, 17 studies on other tumor types, 22 conference papers with abstracts only, 12 phase I studies, 15 ongoing studies, 42 reviews, and 1 comment), 3 RCTs and 12 NRCTs remained. A total of 15 clinical studies were reported in 16 publications ( Figure 1 ) ( Kataoka et al, 2017 ; Shaverdian et al, 2017 ; Tamiya et al, 2017 ; Fiorica et al, 2018 ; Theelen et al, 2019 ; Welsh et al, 2020 ; Hosokawa et al, 2021 ; Metro et al, 2021 ; Samuel et al, 2021 ; Sheng et al, 2021 ; Theelen et al, 2021 ; Öjlert Å et al, 2021 ; Guo et al, 2022 ; Qiang et al, 2022 ; Schoenfeld et al, 2022 ; Wang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…After excluding studies, such as conference abstracts, non-English papers, and non-related interventions, 28 papers, including 12 randomized controlled trials, were finally included in the Bayesian network meta-analysis. A total of 3703 patients received at least one of the five treatment strategies ( Table 1 ) ( 15 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…6 studies recruited less than expected ( 32 , 34 , 35 , 39 41 ), 9 studies did not mention random sequence generation ( 32 , 33 , 35 , 37 42 ), 3 studies did not mention study blinding design ( 31 33 ), and other aspects were assessed as high quality. Table 2 | Of the cohort studies, 12 studies did not specify whether subjects had developed the focused disease ( 15 , 16 , 18 , 20 , 23 , 24 , 26 30 , 36 ), and were rated as high risk, 25 studies only mentioned part follow-up related data ( 15 21 , 23 , 25 30 ), which is not enough to judge the completeness of the follow-up data, and were rated as high risk, and the rest included studies were low risk. We rated articles with a score of ≥ 6 as high quality, and all included studies were high quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations